Efficacy of Trolene 40 insecticidal premix to control grubs in feedlot cattle - Fink, G.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Ninety Angus crossbred steers originating from northwestern Nebraska and averageing 440 lb. were used to evaluate the efficacy of Trolene 40 insecticidal premix to control cattle grubs in feedlot cattle. Thirty steers were randomly assigned to each of these three treatments: (1) control; (2) .0018 lb. runnel/100 lb. body weight per day for 7 days; (3) .0009 lb. runnel/100 lb. body weight for 14 days. The active ingredient was incorporated into a ground-sorghum-grain premix and fed in the complete ration. The trial started November 21; the 14-day feeding ended December 2, 1974. Grub counts were made February 27, 1975. The control steers had 188 grubs for an average of 6.3 grubs per steer. The 7-day treatment group had 10 grubs; the 14 day group, 3 grubs, so control was 95 and 98%, respectively, for the two treatments.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Feedlot cattle; Grubs